UJI KUALITAS DAGING SAPI OTOT BICEP FEMORIS (BF) DI PASAR SANGATTA KUTAI TIMUR KALIMANTAN TIMUR - Tamal, Mey Angraeni; Sutikno, Sutikno; Yance, Yance (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2024)
The purpose of this study is to determine the quality of beef with Bicep femoris (BF) muscle parts traded in the Sangatta markets, East Kutai. This study uses Complete Random Design (RAL) with 3 treatments and 3 replications and the tests carried out are pH test, colour test and TPC test. The treatment consists of 3 markets, namely South Sangatta Market, Teluk Lingga Market, and Main Market. The results showed that the physical quality of beef color in the BF muscle was significantly different, namely Pasar Sangatta Selatan quality II while Pasar Teluk Lingga and Pasar Utama quality I. The results of beef pH analysis in the three markets were not significantly different and were within the normal range. TPC tests on the muscle parts of BF cows in all three markets showed that 63% were below the threshold and 37% were above the threshold. All parties involved in the provision of meat need to pay attention to the cleanliness of the meat.